The Effects of Foot Reflexology on Vital Signs: A Meta-Analysis of Randomized Controlled Trials. (13th September 2022) - Jing, Yunyan; Liu, Shanxin; Pan, Chunqi; Jian, Ying; Wang, Mingwei; Ni, Bin
Abstract : Introduction . We evaluated the effects of foot reflexology on bodily vital signs. Methods . Randomized controlled trials (RCTs) evaluating the effects of foot reflexology on vital signs were collected for a meta-analysis. Statistical analysis was conducted using RevMan5.4 software and pooled estimates of the effects were reported as mean differences (MDs) with 95% conﬁdence intervals (CIs). Results . Thirteen studies, including 819 patients, met our inclusion criteria. Our results showed that systolic blood pressure (SBP) (MD = -4.62, 95% CI: -5.58 to -3.66; P < 0.00001 ), diastolic blood pressure (DBP) (MD = -3.32, 95% CI: -4.48 to -2.17; P < 0.00001 ), heart rate (HR) (MD = -4.76, 95% CI: -6.49 to -3.04; P < 0.00001 ), respiratory rate (RR) (MD = -0.77, 95% CI: -1.50 to -0.48; P < 0.00001 ), and pulse oxygen saturation (SpO2 ) (MD = 0.95, 95% CI: 0.39 to 1.52; P = 0.0009 ) showed statistical significance in the foot reflexology group. Conclusions . Short-term followup results showed that foot reflexology exerted positive effects on vital signs, reduced BP, HR, and RR and increased SpO2 .